Method Performance of Bicarbonate and Electrolytes by Use of Duodenal Fluid for Assessment of Exocrine Pancreatic Function. (15th January 2020) - Pyle-Eilola, Amy; Pagan, Jill; Kayatin, Adam; Povse, Patrick N; Rietschlin, Jacqua A; Cotten, Steven W
Abstract: Background: Evaluation of exocrine pancreatic insufficiency is challenging for both clinicians and laboratories. Indirect pancreatic function tests such as serum trypsinogen, fecal elastase, and fecal fat measurements are moderately sensitive for diagnosis of advanced chronic pancreatitis but show reduced sensitivity and specificity for diagnosis of early disease. An alternative is the endoscopic pancreatic function test, which uses duodenal secretions after administration of IV secretin. Samples are collected at various times via the endoscopic tube and then analyzed for bicarbonate, sodium, potassium, and chloride. Methods: Precision, linearity, method comparison, and stability studies were performed on the Beckman Coulter AU5822 chemistry analyzer with duodenal fluid. Comparison with the Vitros 4600 dry slide chemistry instrument was used to interrogate differences between methods. Results: All assays produced a CV <2% without any measurable effects from the endoscopy fluid matrix and showed acceptable imprecision near the limit of detection (CV < 5%). All analytes showed linear dilution across the analytical measuring range. All the calculated error biases from dilutions were within 50% of the CLIA-allowable error for serum for each of the respective analytes. The calculated slopes ranged from 0.841 to 1.274 when compared to the Vitros 4600. Stability studies demonstrated that sodium, potassium, chloride, and bicarbonate remained stable after storage at −20 °C and after multiple freeze–thaw cycles. The percent change for all analytes was <5% mmol/L. Conclusions: The AU5800 series demonstrated adequate performance for the analysis of bicarbonate in duodenal fluid and therefore can be used for assessment of exocrine pancreatic function. However, notable discrepancies were observed for sodium, potassium, and chloride between the AU5800 series and the Vitros 4600.